New family host and records of Acanthocrios furnarii (Cordero & Vogelsang, 1928) (Hemiptera: Cimicidae) from Argentina, and implications in the transmission mechanism of cimicid bugs among birds’ nests - Iorio, Osvaldo Di; Turienzo, Paola; Bragagnolo, Laura; Santillán, Miguel Ángel; Grande, Juan Manuel (Zootaxa, 2013)
Acanthocrios furnarii (Cordero & Vogelsang, 1928) [Hemiptera: Cimicidae: Haematosiphoninae] is an ectoparasite on avian hosts from Argentina and Uruguay. It has been mostly found in mud nests of Furnarius rufus (Gmelin, 1788) [Aves: Furnariidae], but its true hosts are some of the inquiline birds that use F. rufus nests. These inquiline hosts belong to the families Emberizidae, Hirundinidae, Icteridae, Passeridae, and Troglodytidae. Outside F. rufus mud nests, A. furnarii has been found in nests of other Furnariidae, Hirundinidae, and Passeridae. The present work adds the first nonpasserine host (Falconidae) of A. furnarii, together with new records in La Pampa, Argentina. The transmission mechanism of A. furnarii, together with all other cimicid bugs from Argentina and adjacent countries, is increased considering this new host; and we also take into account the birds that nidificate in nest boxes, the cavity-nesting birds in trees and earth, and the inquiline birds in stick nests of Furnariidae and Psittacidae.